2006
DOI: 10.1080/13854040590947380
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Patients with Epilepsy or Psychogenic Non-Epileptic Seizures on Four Measures of Effort

Abstract: Exaggeration of cognitive symptoms or poor effort on cognitive testing has been addressed primarily in the traumatic brain injury literature. The present investigation aims to extend the evaluation of effort to the epilepsy monitoring setting, where base rates of failure on effort testing remain unknown for patients with intractable epilepsy (ES), psychogenic nonepileptic seizures (PNES), or both conditions (ES+PNES). In addition, this investigation explores how well four measures of effort (DMT, LMT, TOMM, PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…AUC area under the curve, LR likelihood ratio, PPP positive predictive power, NPP negative predictive power consistent with the results of previous studies (Cragar, Berry, Fakhoury, Cibula, & Schmitt, 2006;Dodrill, 2008). The data analysis can be reduced to a number of clinically relevant findings: (1) CIM scores were consistently lower in patients who failed reference PVTs.…”
Section: Discussionsupporting
confidence: 83%
“…AUC area under the curve, LR likelihood ratio, PPP positive predictive power, NPP negative predictive power consistent with the results of previous studies (Cragar, Berry, Fakhoury, Cibula, & Schmitt, 2006;Dodrill, 2008). The data analysis can be reduced to a number of clinically relevant findings: (1) CIM scores were consistently lower in patients who failed reference PVTs.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Locke et al 125 showed that performance on the TOMM had a better correlation with cognitive outcomes than did neuropathology or psychopathology. However, Cragar et al 126 used four different symptom validity tests including the PDRT, Digit Memory Test, Letter Memory Test, and TOMM, showing similar poor effort in PNES (N=21; 24%), ES (N=41; 22%), and PNES plus ES (N=18; 11%); these results suggest that these measures would not be useful in discriminating clinical diagnostic categories. Williamson et al 127 showed that failure on the WMT among patients with PNES (N=90; 35%) was associated with a history of physical or emotional abuse (reported as yes or no to the different abuse types) and was not associated with obvious financial incentive.…”
Section: Cognitionmentioning
confidence: 99%
“…A Dutch study of nearly 2000 healthy subjects found that as many as 29% of people aged [25][26][27][28][29][30][31][32][33][34][35] considered themselves forgetful, rising to 34% (40-50 years), 41% (55-65) years and 52% between 70-85 years [3]. High proportions (47-60%) of these respondents said they were worried to some extent about their forgetfulness Complaints of forgetfulness were correlated with depression and poor subjective health.…”
Section: Memory Symptoms In the General Populationmentioning
confidence: 99%